Female genital mutilation; culture, religion, and medicalization, where do we direct our searchlights for it eradication: Nigeria as a case study - Olalekan Olugbenga Awolola; N A Ilupeju (Tzu Chi Medical Journal)
Female genital mutilation (FGM) is a form of violence against the girls and the women and also an infringement into the rights of the women in the society. It is practiced mostly in Africa, but migration has revolutionized its spread to almost all parts of the world. The government and the constituted authorities, our traditional rulers, the legislative, the judiciary, and the law enforcement agents have the machineries to stop this inhuman behavior, but they lack the will and the necessary information about the incidence and consequences of FGM. The review involved Internet and literature search mostly those written on the African continent and some that were specific to Nigeria from 1999 to 2018. This article reviewed the spread, the obstetrics and the gynecological complications, the roles of the traditional circumcisers, and the negative and the positive roles of the caregivers, especially its medicalization in the abandonment of FGM in Nigeria. The article also looked critically at the best ways to achieve zero tolerance to FGM. To achieve the targeted zero tolerance to FGM, the identified factors have to be tackled holistically.